Penerapan Model Discovery Learning Materi Giving Opinion pada Siswa Kelas XI dengan Menggunakan Media Gambar - Meiliawati, Evi (Yayasan Sembilan Pemuda Indonesia, 2022)
The research aims to improve learning outcomes of giving opinion in English through the Discovery Learning model. The data sources of this research were students of class XI IPA 1 Madrasah Aliyah Negeri 1 Bengkulu City, totaling 32 students. The time of this research was carried out in the first semester of the 2019/2020 academic year for 4 months. The data collected are quantitative and qualitative data. Quantitative data is data obtained from formative test results in each cycle. While qualitative data in the form of observations in each learning cycle. The data obtained is converted to the success criteria to determine whether student learning outcomes can be seen how the improvement. The results of the study revealed that in the Pre-cycle the average value of students was 59.84 with 13 of 32 students who completed the cycle. I, which was 69.38 with 17 students who finished then in the second cycle it increased again, namely 82.81 with 28 students who completed from 32 students in class XI IPA 1 Madrasah Aliyah Negeri 1 Bengkulu City. The percentage of KKM achievement also increased from 40.63% in the pre-cycle, increased in the first cycle of 53.13% and increased again to 87.50% in the second cycle. The conclusion is that efforts to improve English learning outcomes for giving opinion materials by applying the Discovery Learning model have been proven to improve student learning outcomes in lessons well so that they are feasible to be applied at Madrasah Aliyah Negeri 1 Bengkulu City.